Note on parity factors of regular graphs - Hongliang Lu; Yuqing Lin (Electronic Journal of Graph Theory and Applications (EJGTA), 2013)
In this paper, we obtain a sufficient condition for the existence of parity factors in a regular graph in terms of edge-connectivity. Moreover, we also show that our condition is sharp.